An Cost-effectiveness analysis of antihypertensive therapy: nifedipine SR–candesartan compared with amlodipine–ramipril in hypertensive patients at Ciracas Regional Hospital - Dini Nabilah; Santi Purna Sari; Marlina Dewiastuti (Universitas Ahmad Dahlan, 2026)
Hypertension is one of the main causes of mortality and morbidity in Indonesia and generally occurs asymptomatic and thus frequently referred to as the silent killer. Long-term therapy is essential, as uncontrolled hypertension can worsen the health and economic status of those affected. First-line therapies recommended by the Joint National Committee’s Eighth Report (JNC 8) include thiazide diuretics, Angiotensin-Converting Enzyme (ACE) inhibitors, Angiotensin II Receptor Blockers (ARBs), and Calcium Channel Blockers (CCBs). The aim of this study was to analyze cost-effectiveness nifedipine sustained release-candesartan compared to amlodipine-ramipril in hypertensive patients. This study was a cross-sectional with primary data obtained from medical records and structured questionnaires prospectively for utility value and adherence level. Total sample of eighty-six outpatients with hypertension fulfill inclusion and exclusion criteria and based on analysis showed that intervention (43 patients) and comparator (43 patients) groups are matching. The results showed that the efficacy of achieving blood pressure control with the nifedipine SR-candesartan combination, as per JNC 8 guidelines, was 48.8% with an Average Cost Effectiveness (ACER) of IDR 6,374. In comparison, the amlodipine-ramipril combination achieved an efficacy of 34.9% with an ACER of IDR 7,421 (p=0.19). The utility gained by patients in the intervention group was higher compared to the comparator group (p=0.004). Hence, it can be concluded that the nifedipine SR-candesartan combination is more cost-effective compared to the amlodipine-ramipril combination.